Infections by multidrug-resistant Gram-negative bacteria: what's new in our arsenal and what's in the pipeline? - Koulenti, Despoina; Song, Andrew; Ellingboe, Aaron; Abdul-Aziz, Mohd Hafiz; Harris, Patrick; Gavey, Emile S.; Lipman, Jeffrey (Elsevier B.V., 2019)
The spread of multidrug-resistant bacteria is an ever-growing concern, particularly among Gram-negative bacteria because of their intrinsic resistance and how quickly they acquire and spread new resistance mechanisms. Treating infections caused by Gram-negative bacteria is a challenge for medical practitioners and increases patient mortality and cost of care globally. This vulnerability, along with strategies to tackle antimicrobial resistance development, prompts the development of new antibiotic agents and exploration of alternative treatment options. This article summarises the new antibiotics that have recently been approved for Gram-negative bacterial infections, looks down the pipeline at promising agents currently in phase I, II, or III clinical trials, and introduces new alternative avenues that show potential in combating multidrug-resistant Gram-negative bacteria.